Impact of tumor size on survival outcome of pancreatic carcinoma following pancreatic resection: A systematic review and meta-analysis - Shrestha, Anuj; Baskota, Attit; Li, Fu Yu; Ma, Wen-Jie; Yang, Qin; Jie, Hu-Hai; Bijukchhe, Sunil Man (Asian Journal of Medical Sciences, 2018)
The aim of the study was to evaluate the influence of tumor size on long-term survival outcome of pancreatic tumors following pancreatic resection and the possibility of implementing another tumor size cut-off point in AJCC pancreatic tumor staging. Literature searches was conducted on electronic database to identify relevant studies on tumor size related survival outcome following pancreatic resection for pancreatic adenocarcinoma. Meta-analysis was done using the effect estimates and the use of 95% confidence intervals (CIs) was done to calculate the pooled risk estimates; heterogeneity among studies was examined using I2 statistic. Total of 18 trials (13 retrospective and 5 prospective studies) including 6230 elderly patients was included in this study. The pooled HR of the tumor size with 2 cm cut-off was 1.43 with 95% CI of [1.27-1.62], I2= 17%, p